2022
DOI: 10.1007/s41109-022-00474-y
|View full text |Cite
|
Sign up to set email alerts
|

Network loss following the 2016 Presidential Election among LGBTQ+ adults

Abstract: Growing levels of political polarization in the United States have been associated with political homogeneity in the personal networks of American adults. The 2016 Presidential Election in the United States was a polarizing event that may have caused further loss of connections to alters who had different politics. Kinship may protect against loss of politically different ties. Additionally, loss of ties with different political views may be particularly pronounced among LGBTQ+ people as they are more likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…A longitudinal study found that some individuals change their political beliefs to match those in their networks (Lazer et al, 2010). Others may adjust their networks when new social and political challenges arise (Facciani & McKay, 2022). Blanchar and Norris (2021) found that political homogeneity in one's network predicted attitudes toward voter fraud and this association between networks and attitudes grew stronger over time.…”
Section: How Network Homogeneity Influences Political Polarization An...mentioning
confidence: 99%
“…A longitudinal study found that some individuals change their political beliefs to match those in their networks (Lazer et al, 2010). Others may adjust their networks when new social and political challenges arise (Facciani & McKay, 2022). Blanchar and Norris (2021) found that political homogeneity in one's network predicted attitudes toward voter fraud and this association between networks and attitudes grew stronger over time.…”
Section: How Network Homogeneity Influences Political Polarization An...mentioning
confidence: 99%